Pain in children - McGrath, Patricia (Henry Stewart Talks, 2009)
Post-surgery pain treatment in children, Clinical studies, Common misbelieves, Impact of untreated pain, Increased plasticity, Situational factors, Minimizing acute pain, Age and developmental trends, Chronic pain problems, Pain clinic repertoire, Complex regional pain syndrome, Behavioral, cognitive and emotional factors, Chronic pain management